2003
DOI: 10.1002/rcm.968
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen isotopomer site preference of N2O produced by Nitrosomonas europaea and Methylococcus capsulatus Bath

Abstract: The relative importance of individual microbial pathways in nitrous oxide (N(2)O) production is not well known. The intramolecular distribution of (15)N in N(2)O provides a basis for distinguishing biological pathways. Concentrated cell suspensions of Methylococcus capsulatus Bath and Nitrosomonas europaea were used to investigate the site preference of N(2)O by microbial processes during nitrification. The average site preference of N(2)O formed during hydroxylamine oxidation by M. capsulatus Bath (5.5 +/- 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
169
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(183 citation statements)
references
References 35 publications
14
169
0
Order By: Relevance
“…The ranges of d 15 N bulk -N 2 O from soil AOA were similar to those (-10 to -50%) from agricultural soils and forest soils (Kim and Craig, 1993;Rahn and Wahlen, 2000;Pérez et al, 2001;Rock et al, 2007). Previous studies found that the d 15 N bulk -N 2 O values of marine AOB (Nitrosomonas marina C-113) were about -10% with 20% O 2 concentration (Frame and Casciotti, 2010), whereas the d 15 N bulk -N 2 O values of N. europaea (ATCC 19718) in ammonia-oxidizing and nitrite-reducing conditions were -46.5% and -34.0%, respectively (Sutka et al, 2003(Sutka et al, , 2006. Surprisingly, the d 15 N bulk -N 2 O values of a marine AOA strain CN25 were positive (8.7%) (Santoro et al, 2011), which differed significantly from the ideal isotope fractionation effect and from those of the soil AOA strains.…”
Section: Aoa Strainsmentioning
confidence: 95%
See 3 more Smart Citations
“…The ranges of d 15 N bulk -N 2 O from soil AOA were similar to those (-10 to -50%) from agricultural soils and forest soils (Kim and Craig, 1993;Rahn and Wahlen, 2000;Pérez et al, 2001;Rock et al, 2007). Previous studies found that the d 15 N bulk -N 2 O values of marine AOB (Nitrosomonas marina C-113) were about -10% with 20% O 2 concentration (Frame and Casciotti, 2010), whereas the d 15 N bulk -N 2 O values of N. europaea (ATCC 19718) in ammonia-oxidizing and nitrite-reducing conditions were -46.5% and -34.0%, respectively (Sutka et al, 2003(Sutka et al, , 2006. Surprisingly, the d 15 N bulk -N 2 O values of a marine AOA strain CN25 were positive (8.7%) (Santoro et al, 2011), which differed significantly from the ideal isotope fractionation effect and from those of the soil AOA strains.…”
Section: Aoa Strainsmentioning
confidence: 95%
“…. SP, the position-dependent isotope value of N 2 O, is an isotopic signature that is commonly used to interpret the source of N 2 O production (Toyoda and Yoshida, 1999;Sutka et al, 2003;Ostrom and Ostrom, 2011). Studies using pure AOB cultures have indicated that a positive SP (30-38%) is consistent with a N 2 O source from hydroxylamine oxidation (ammonia oxidation), whereas nitrifier denitrification (and denitrification) is thought to produce N 2 O with a SP value near or below zero (-10 to 0%) (Frame and Casciotti, 2010;Sutka et al, 2006).…”
Section: Aoa Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…SP, which is independent of the substrate's isotopic signature, has unique values reflecting microbial production pathways. SPs of N 2 O produced by NH 2 OH oxidation and by NO 2 -reduction were respectively about 33‰ and 0% [15][16][17][18] that can be a robust parameter in the analysis of mechanisms. In the last years, several efforts have been made to better understand the mechanisms of N 2 O production based on the isotopomer ratios of N 2 O in complex bacterial system during wastewater treatment [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%